Pembiayaan Berparadigma Green Financing Dalam Pengembangan Ekonomi Berkelanjutan - Yutisa Tri Cahyani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Introduction: This study aims to explore the green financing paradigm in the context of Islamic banking and to analyze the implementation of green financing in the Islamic banking sector in Indonesia. The green financing paradigm refers to a financial approach that considers aspects of environmental sustainability in the context of channeling funds based on Sharia principles. Research Methods: The methods used in this study include literature analysis to understand the concepts and theories related to green financing in Islamic banking and analysis of financial statements of PT BSI and PT BCA Syariah to explore the implementation of green financing in these institutions. Results: This study identifies the extent to which Islamic banks in Indonesia have adopted the green financing paradigm, the factors that influence its implementation, and its impact on environmental and social sustainability in Indonesia. Conclusion: This research is expected to provide an in-depth understanding of the role of Islamic banking in supporting sustainable development, particularly in the environmental context in Indonesia. The results are expected to be the basis for policy development supporting green financing growth in the Islamic banking sector.